The performance trend of Davao Oriental State College of Science and Technology (DOSCST) in board licensure examination for Professional teachers - Arvin Andacao; Maria Gloria Lugo (Davao Research Journal)
The Institute of Education and Teacher Training provides quality teaching and prepares students for life and teaching career. However, graduates of this program must pass the Board Licensure Examination for Professional Teachers (BLEPT) to practice the profession, which challenges the institution to produce professionals and beat national standards. Hence, this study aims to analyze the trend of Davao Oriental State College of Science and Technology (DOSCST) performance in the licensure examination for professional teachers supervised by the Professional Regulation Commission. The authors employed archival quantitative research to analyze records and data results. The subject of the investigation was performance passing rates covering from 2010 to 2021 treated with frequencies, percentages, and differences. The findings revealed that all programs performed at least 50% passing rates and higher than the national passing percentage. The elementary program indicated 67.03%, secondary level marked 71.33%, and BPE-SPE gained 75.18% passing rates for first takers. Further results found that the elementary and secondary teacher education indicated 20% to 49.99% passing rates with less than the national passing scores. Finally, the school's overall performance passing rates went beyond the national passing rates. Meanwhile, both elementary and secondary programs earned many overall turnouts compared to the BPE-SPE program. Establishing a free academic clinic to coach and mentor the repeaters as part of extension activities and application of success predictors to improve licensure examinations is hereby recommended.